Design, synthesis, and biological evaluation of some novel indolizine derivatives as dual cyclooxygenase and lipoxygenase inhibitor for anti-inflammatory activity - Shrivastava S.K.; Srivastava P.; Bandresh R.; Tripathi P.N.; Tripathi A. (My University, 2025)
Some novel indolizine derivatives were synthesized by bioisosteric modification of imidazo[1,2-a]pyridine for anti-inflammatory activity. The physicochemical characterization and structure of compounds were elucidated by state of the art spectroscopic technique. Induced fit docking was performed for initial screening to elucidate the interactions with corresponding amino acids of cyclooxygenase (COX-1, COX-2) and lipoxygenase (LOX) enzymes. The target compounds 53–60 were then evaluated against in vivo carrageenan and arachidonic acid induced rat paw edema models for anti-inflammatory activity. Amongst all the synthesized derivatives, compound 56 showed the significant anti-inflammatory activity in both rat paw edema models with very less ulcerogenic liability in comparison to standard diclofenac, celecoxib, and zileuton. The compounds 56 was further assessed to observe in vitro enzyme inhibition assay on both cyclooxygenase and lipoxygenase enzyme where it showed a preferential and selective non-competitive enzyme inhibition towards the COX-2 (IC50 = 14.91 μM, Ki = 0.72 µM) over COX-1 (IC50 > 50 μM) and a significant non-competitive inhibition of soybean lipoxygenase enzyme (IC50 = 13.09 μM, Ki = 0.92 µM). Thus, in silico, in vivo, and in vitro findings suggested that the synthesized indolizine compound 56 has a dual COX-2 and LOX inhibition characteristic and parallel in vivo anti-inflammatory activity in comparison to the standard drugs. © 2017 Elsevier Ltd